(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
Indigenous Nigerian society respect and believe so much in her elderly. Males and female elderly are transmitters of traditional norms and values in a sustainable manner in each community. As such, they are the sage and kingmakers appointing, decision makers through careful and flawless selection from character check overtime, delving into family history and divination of the traditional oracle. After coronation, such leaders are never corrupt; they live up to expectation by promoting the wellbeing of the masses. However, this practice has been eroded by colonization and westernization for a democratic way of appointing leaders through voting; as such countries design voter education for her citizenry. This study thus examined voter education as a determinant of voting pattern of indigenous elderly women in Akoko land through these research questions: (i) what is the demographic characteristics of the elderly women in the study area? (ii) What kind of voter education programmes is available on the selected radio stations? (iii) What is the level of participation of the women on the programme on radio? (iv) To what extent has the women benefited from their participation in voter education programme on radio? (v) How has the voter education received influenced the voting pattern of the women? The study adopted the descriptive survey research through multi stage sampling technique by purposively selecting sixty indigenous elderly women from areas of the four Local Government ( Okorun, Ese, Agbaluku, Iwaro-Oka, Supare, Oba, Erusu, Okeagbe. Findings of the study showed that voter education in the study area impacted minimally on the respondents resulting in their skewed knowledge and voting pattern (Grand mean 2.71+2.46+2.19+2.13=116.9/4=29.2). It is recommended among others that voter education should include indigenous education, a larger coverage and quality.